'I was just gobsmacked': care workers responses to BBC Panoramas 'Undercover care: the abuse exposed': invoking mental states as a means of distancing from abusive practices - Patterson, Anne; Fyson, Rachel (SAGE, 2016)
This paper draws upon discourse analytic techniques and discursive psychology to examine how care workers build accounts of viewing the BBC Panorama programme “Undercover Care: The Abuse Exposed” which graphically documented the abuse of people with learning disabilities in a residential care setting. 56 interviews were conducted as part of a project concerning adult safeguarding. The analysis considers how careworkers report their reactions and the interactional strategies they use to construct themselves as shocked and disbelieving and thus, as oppositional to the extreme practices in the programme. Their role as careworkers, and therefore as ‘insiders’ of the industry that allowed such abuse to happen, makes matters of stake and agency live issues for this particular group; and constructions of ‘shock’ and ‘disbelief’ are potential ways for participants to distance themselves from the abuse shown in the programme. More broadly, these data show how the invocation of mental states contributes to the management of other discursive business, namely, that of fending off any association with the aforementioned extreme practices.